Aesthetic Quality of Island Tourism in Malaysia's East Coast Region: Does Duration of Stay Matter in Satisfying Tourists? - Saad, Mazni; Lokman, Ainun Khadijah; Ong, Mohd Hanafi Azman; Othman, Nor'Ain (2021)
The East Coast islands of Malaysia are becoming increasingly popular as a world-class nature tourism destination. Not only are they naturally beautiful and accessible, they are also attractive and appear as a destination image. However, whether satisfaction based on the aesthetic quality of the island is sufficient in determining a tourist’s duration of stay is being questioned. This study, therefore, sets out two objectives to investigate the relationship between Aesthetic qualities and Tourist Satisfaction which are to investigate which aesthetic quality has a significant influence on tourist satisfaction of Malaysia’s East Coast islands and to determine whether the length of stay has a significant influence on tourist satisfaction of the East Coast islands of Malaysia. This study used both quantitative and cross-sectional methods to collect data. Then a Smart PLS-SEM analysis was used on the 150 responses; the 5000 replication of samples reveals that all aesthetic qualities contributed to tourist satisfaction. The ANOVA analysis, supported by the post hoc multiple comparison analysis among the groups, the Least Square Difference (i.e., LSD) Fisher’s Test, and Games-Howell Test, yielded intriguing results for the significant difference between the duration of stay groups on these islands. All aesthetic qualities, especially scenery, showed significant differences during a short stay. The findings would raise public awareness of the importance of sustaining the aesthetic quality of island tourism while also benefiting many stakeholders. There is also a need for more promotional efforts to extend the tourists’ duration of stay. However, generalisations of the results of this study are limited to responses given mainly from three main islands of Terengganu.